2022
DOI: 10.36348/sjef.2022.v06i09.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cash Flow, Board Independence, and Company Size on Financial Distress

Abstract: Covid-19 has affected the world’s economic sectors, including Indonesia. This can be seen from the declining of the company’s operational activities until the threat of the company to become bankrupt, so that it can influence the stability of the country. The government tries its best to recover the economy. Therefore, the objective of this research is to test the effect of cash flow, board independence, and company size on financial distress. It is classified as causal research with quantitative approach. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…This accords perfectly with our a priori expectation of a positive relationship between board independence and conservative reporting based on theoretical underpinning that the independence of a board of directors positively influences the extent to which policy matters are handled without undue influences and biases from persons internal to the organization. Since the independence of the board is influenced by its composition, it has been advocated that non-executive directors should be in the majority in other to enhance its independence (Fransisco & Fitria, 2022). Consistent with the findings of this study.…”
Section: Board Independence and Accounting Conservatismsupporting
confidence: 90%
“…This accords perfectly with our a priori expectation of a positive relationship between board independence and conservative reporting based on theoretical underpinning that the independence of a board of directors positively influences the extent to which policy matters are handled without undue influences and biases from persons internal to the organization. Since the independence of the board is influenced by its composition, it has been advocated that non-executive directors should be in the majority in other to enhance its independence (Fransisco & Fitria, 2022). Consistent with the findings of this study.…”
Section: Board Independence and Accounting Conservatismsupporting
confidence: 90%
“…Thus, it resulted in ineffective and inefficient operational activities. This conclusion was in line with Permana & Umiyati (2022) and Ombaba & Kosgei (2017) which stated that financial distress was influenced by board size.…”
Section: Influence Of Board Size On Financial Distresssupporting
confidence: 89%
“…This means that companies that generate cash positively are able to fulfill obligations on debt and guarantee company operations, and of course can avoid financial distress. Meanwhile, according to research (Nasution, 2019), and (Pandapotan & Puspitasari, 2022b)revealed a positive effect of cash flow on financial distress significantly.…”
Section: Cash Flow On Financial Distressmentioning
confidence: 95%